Pengaruh Jumlah Pembayar Pajak Parkir Yang Patuh, Jumlah Lahan Parkir, dan Jumlah Penerimaan Pajak Parkir Terhadap Pendapatan Asli Daerah Kota Yogyakarta - Dwi Santoso (JURNAL EKOBIS DEWANTARA, 2018)
This study aims to determine the effect of the number of obedient parking taxpayers, the amount of parking space, and the amount of tax revenue parking to the original revenue area Yogyakarta city. The nature of this research is quantitative research. Sources of data used are secondary data obtained from the BPKAD of Yogyakarta. The population in this study is the number of taxpayers, the amount of parking space, parking realization tax report and realization reports original revenue area of Yogyakarta. The sample used is the number of obedient parking taxpayers, the number of registered parking lots, the report of the realization of parking tax, and the realization of original revenue area of Yogyakarta. Data analysis in this study used multiple linear regression with SPSS program version 16.0. The results showed that the value of F arithmetic 10.072 greater than the value of F table 2.90 with significance 0.00 <0.05. This indicates that the the number of obedient parking taxpayers (X1), the amount of parking space (X2), and the amount of parking tax (X3) influence simultaneously to the original revenue area of Yogyakarta. Partially parking tax (X3) have a significant positive effect on original revenue area of Yogyakarta city. This is evidenced by the significance of 0.014 <0.05 and the value of t arithmetic 2.611> t table 1.694. Although the value of t arithmetic 1.977> t table 1.694 but the number of obedient parking taxpayers (X1) does not affect the original revenue area of Yogyakarta. This is evidenced by the significance of 0.057> 0.05. The amount of parking space (X2) does not affect the PAD of Yogyakarta city. This is evidenced by the significance of 0.221> 0.05 with t arithmetic 1,249 <1.694.